2021
DOI: 10.1021/acsanm.1c03361
|View full text |Cite
|
Sign up to set email alerts
|

Pt Nanoparticles on ZSM-5 Nanoparticles for Base-Free Oxidation of 5-Hydroxymethylfurfural to 2,5-Furandicarboxylic Acid

Abstract: 5-Hydroxymethylfurfural (HMF) is considered as a valuable platform chemical derived from abundant sugars in a plant-based biomass. One of the most precious chemicals, which can be derived from HMF, is 2,5-furandicarboxylic acid (FDCA), which is a renewable substituent for petroleum-based terephthalic acid. Herein, the selective oxidation of HMF to FDCA and its derivatives has been accomplished using highly dispersed Pt nanoparticles supported on alkaline-exchanged hierarchical ZSM-5 nanoparticles under mild co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…The conversion remained unchanged after raising the catalyst dosage to 30 and 40 mg (120 wt % and 160 wt % loading, respectively); however, the FDCA yield increased slightly, and no byproducts were observed. Thus far, the previous studies have reported the catalyst loading in the range of 170–380 wt %, to obtain an 80–99% FDCA yield under homogeneous base-free conditions. ,,, However, some works were done using Pt- and Au-based catalysts at the 60–80 wt % loading, but Pt and Au are at least 3 times more expensive than Ru. ,, …”
Section: Resultsmentioning
confidence: 99%
“…The conversion remained unchanged after raising the catalyst dosage to 30 and 40 mg (120 wt % and 160 wt % loading, respectively); however, the FDCA yield increased slightly, and no byproducts were observed. Thus far, the previous studies have reported the catalyst loading in the range of 170–380 wt %, to obtain an 80–99% FDCA yield under homogeneous base-free conditions. ,,, However, some works were done using Pt- and Au-based catalysts at the 60–80 wt % loading, but Pt and Au are at least 3 times more expensive than Ru. ,, …”
Section: Resultsmentioning
confidence: 99%
“…A total conversion of HMF with 80 % of FDCA yield was achieved at 100 °C and 2.0 MPa of air. [55] NaY zeolites were used as support for Ru nanoparticles. The 3 wt% Ru-NaY catalyst demonstrated excellent catalytic performance with complete HMF conversion and 94 % yield of FDCA in 8 h (1 MPa O 2 , 120 °C) and good recyclability (4 cycles).…”
Section: Base-free Catalytic Systemsmentioning
confidence: 99%
“…For example, highly dispersed Pt nanoparticles were incorporated on alkaline‐exchanged hierarchical ZSM‐5. A total conversion of HMF with 80 % of FDCA yield was achieved at 100 °C and 2.0 MPa of air [55] . NaY zeolites were used as support for Ru nanoparticles.…”
Section: Metal‐based Catalysismentioning
confidence: 99%
“…Therefore, various strategies for HMF oxidation reactions have been developed to selectively obtain FDCA in high conversion yields for thermal heterogeneous catalysis, , electrocatalysis, , photocatalysis, , microwave heating, and enzyme catalysis . Among these various strategies, the thermally heterogeneous catalysts that utilize molecular oxygen (O 2 ) as an oxidant have garnered significant research interest because of their eco-friendly, cost-effective, and efficient characteristics. Recently, a number of heterogeneous catalyst systems decorated with nanosized noble metals have been reported for the reaction under base-free conditions. Wang et al reported that the alloying effect for the Au–Pd/CNT catalysts not only improved the catalytic properties but also changed the reaction pathway in comparison with the Au/CNT catalyst under base-free conditions . Basic supports such as La–CaMgAl–LDH or nNiO have also been used as carriers for the Au–Pd bimetallic catalysts; AuPd/La–CaMgAl–LDH or AuPd/nNiO could catalyze the oxidation of HMF in the absence of alkaline additives .…”
Section: Introductionmentioning
confidence: 99%